Pengembangan E-Modul Sani (Social and Natural Sciences) untuk Meningkatkan Kemampuan Berpikir Kreatif dan Kritis pada Siswa Kelas 4 di SD Sedayu Bantul - Sani Sani (Jurnal Pendidikan Indonesia, 2025)
This study aims to develop and evaluate the feasibility of the SANI E-Module (Social And Natural Sciences) in enhancing the creative and critical thinking skills of fourth-grade elementary school students. The research method used is Research and Development (R&D) with the ADDIE model, which consists of five stages: analyze, design, develop, implement, and evaluate. The results indicate that the SANI E-Module is highly feasible based on the assessment of material experts (3.76), media experts (3.70), and user responses (3.60). Additionally, the implementation of this module effectively enhances students' creative and critical thinking abilities, as evidenced by an increase in the average score of 14.73 after its use. The SANI E-Module also provides a more interactive and engaging learning experience through enriched visuals and videos, while fostering students' digital skills.